WINGKO INDUSTRY SUSTAINABILITY IMPROVEMENT STRATEGY USING THE BUSINESS MODEL CANVAS (BMC) METHOD - Khoirul Hidayat; Firman Arief Soejana; M Fuad Fauzul Mu'tamar (Journal of Industrial Engineering Management, 2021)
Wingko is one of Indonesian Snack from Babat of Lamongan Regency which is produced by UMKM Klapa Muda. Compete makes the production unstable, even decreased. Right now UMKM Klapa Muda must develop rapidly, because there are already many competitors selling similar products. In this study using the Business Model Canvas Development that is assisted using the Internal factor Evaluation matrix, External Factor Evaluation, Internal-External, SWOT matrix analysis, and QSPM (Quantitative Strategic Planning Matriks) analysis. For the weighting stage, 5th priority strategies used for market penetration and product development by applying Business Model Canvas (BMC) concept to UMKM Klapa Muda Babat strategy, it is 1) Customer Relationship Increasing promote activities with a value of 2,401, 2) Customer Segments establish customer loyalty with a value of 2,386, 3) Value Proposition guarantees production quality and mproves products with a value of 2.24, 4) Channels has a relationship with the government with a value of 2,015, 5) Key Resources Development of machine and equipment technology with a value of 1,308.